An Analysis of the Non-conformities of Certified Companies Operating in Northwestern Russia - Maxim Trishkin; Timo Karjalainen; Jyrki Kangas (Forests, 2019)
Research Highlights: The majority of non-conformities (NCs) occurred under environmental impact (Principle 6) in all regions, and contributed on average to 40% and 48% of the total number of minor and major NCs respectively. Background and Objectives: The performance of certified companies operating has been frequently criticized in Russia. The aim of this study was to analyse the NCs of FSC (Forest Stewardship Council) -certified companies in northwestern (NW) Russia during the period 2011–2015. Materials and Methods: In total, 69 FSC certificates were assessed, representing 112 FSC-certified companies. It should be noted that the number of certificates in this study increased 2.4-fold (from 29 to 69) during the period 2011–2015. At the same time, the number of minor NCs increased only 1.6-fold (from 221 in 2011 to 363 in 2015), while the number of major NCs increased 3.4-fold (from 25 in 2011 to 84 in 2015). Results: During the five-year period, the highest number of NCs was issued in the Arkhangelsk region and in Republic of Karelia, followed by the Vologda region. On the contrary highest number of issued NCs both minor and major per 1000 ha of certified area was in the Novgorod region. The data were also analyzed on leaseholder level and preliminary split into three categories. Conclusions: The number of NCs was, on average, higher for large-sized leaseholders for both the major and minor NCs in comparison to medium- and small-sized leaseholders. However, there were no significant statistical differences observed.